STRATEGY FOR IMPROVING LEMONGRASS AGRICULTURE BASED ON SMART FARMING IN JATIJEJER VILLAGE - Gondokesumo, Marisca Evalina; Azminah; Ardiansyahmiraja, Bobby; Suryaningsih, Retna (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
Lemongrass (Cymbopogon citratus) and citronella (Cymbopogon nardus L.) are flagship crops cultivated by farmers in Jatijejer Village. Lemongrass is commonly used as a culinary spice, while citronella is widely utilized for producing essential oil rich in citronellal, geraniol, and citronellol. The essential oil from citronella has high economic value due to its applications in the cosmetics and health industries. This community service activity aims to enhance local farmers' understanding and skills in proper lemongrass cultivation and the potential processing of essential oils as value-added products. The program focuses on strategies to optimize agricultural potential using proper cultivation techniques with organic farming systems based on smart farming technology. Farmers were educated on the stages of lemongrass cultivation, including land preparation, planting, crop maintenance, fertilization, pest and disease control, as well as harvesting and post-harvest handling. Participants were given pre-tests and post-tests to assess their understanding. The test results showed a significant improvement in participants' comprehension of proper lemongrass cultivation using smart farming methods, as well as the benefits and processing of essential oils. This activity successfully raised awareness of the importance of innovation in the agricultural sector and laid the foundation for the development of local businesses based on natural resources.